Kepuasan Pelanggan Terhadap Kualitas Pelayanan Jaksa Agung Muda Bidang Perdata dan Tata Usaha Negara (Jam Datun) Kejaksaan Agung Republik Indonesia - Asep Mulyana; Mulyati, Heti; Setiawan, Alim (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
The Attorney General's Office of the Republic of Indonesia is the government institution that carries out services in civil and administrative matters whereby the Deputy Attorney General for Civil and Administrative Matters (Jam Datun) executes the task. This research is to ascertain customer satisfaction toward the quality of Jam Datun's services by analyzing the variable of service that are important to service user satisfaction and the Jam Datun’s service user satisfaction level. This research utilizes the saturated sampling method with online survey techniques to all Jam Datun Service users in 2021, which amounted 82 service users that is Government institution, State-owned enterprises, Subsidiaries of State-owned enterprises and their affiliates, as well as consortia of State-owned enterprises. The data obtained has been processed using the Importance Performance Analysis (IPA) method and Customer Satisfaction Index (CSI). The results of the IPA analysis showed that the essential attributes based on service users' perceptions are Clarity of information on the stages of handling cases or legal services and Excellencies of accomplishing the legal services to certain legal matters. The results of CSI analysis are 85.58% indicating that the index of service users’ satisfaction in Jam Datun is "Extremely Satisfied." Keywords: jam datun, importance performance analysis, customer satisfaction index, the attorney general's office of the republic of indonesia, service